Slow rusting in groundnut genotypes against Puccinia arachidis - SRIKANT KULKARNI, GURURAJ SUNKAD* and (Indian Phytopathology, 2008)
The slow rusting ability of twentyone groundnut genotypes was studied against Puccinia arachidis. Ten genotypes viz., Dh-22 (Red), Dh-22 (Tan), GPBD-4, K-134, R-8808, R-9214, R-9227, R-2001-1, R2001-2 and R-2001-3 showed longer latent period, lesser number of pustules per unit area, smaller pustules, low amount of uredospores/pustule, lesser percent disease index), rate of infection and area under disease progress curve compared to fast rusting genotypes and were categorized as slow rusters.